2016
DOI: 10.2147/ppa.s100844
|View full text |Cite
|
Sign up to set email alerts
|

A renewed Medication Adherence Alliance call to action: harnessing momentum to address medication nonadherence in the United States

Abstract: The problemNonadherence to prescription medications is a common and costly problem with multiple contributing factors, spanning the dimensions of individual behavior change, psychology, medicine, and health policy, among others. Addressing the problem of medication nonadherence requires strategic input from key experts in a number of fields.Meeting of expertsThe Medication Adherence Alliance is a group of key experts, predominately from the US, in the field of medication nonadherence. Members include represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This information is important to a variety of stakeholders in both the public and private sector, including local, state and federal public health and policy officials and pharmacy retailers, interested in better understanding the role of pharmacies in improving access and adherence to prescription medications. Although policy efforts—such as Medicare Part D—have focused on ensuring the affordability of prescription medications [ 18 ], non-adherence, which varies across localities [ 5 , 6 ], persists as important public health problem in the U.S. [ 19 ], suggesting access barriers, including pharmacy accessibility and the provision of pharmacy accommodations associated with access to prescription medications, are also important to consider.…”
Section: Discussionmentioning
confidence: 99%
“…This information is important to a variety of stakeholders in both the public and private sector, including local, state and federal public health and policy officials and pharmacy retailers, interested in better understanding the role of pharmacies in improving access and adherence to prescription medications. Although policy efforts—such as Medicare Part D—have focused on ensuring the affordability of prescription medications [ 18 ], non-adherence, which varies across localities [ 5 , 6 ], persists as important public health problem in the U.S. [ 19 ], suggesting access barriers, including pharmacy accessibility and the provision of pharmacy accommodations associated with access to prescription medications, are also important to consider.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Not surprisingly, efforts to better understand the determinants and facilitators of, and challenges to, adherence have proliferated in medicine and social science, contributing to a robust body of literature that can seem overwhelming. 4 In response to the ongoing need to optimize work with patient medication adherence in a manner that leverages social-behavioral science, the University of Alabama at Birmingham (UAB) hosted a conference, BUnderstanding and Improving Treatment Adherence: An Interdisciplinary Approach,^in February 2016. Our review and discussion of social-behavioral models of medication adherence provides a rationale for their wide-scale use, a brief sampling of HIV medication adherence models that can be generalized to other conditions and regimens, a synthesis of salient factors identified across multiple models, and practical recommendations for using evidence-based and evidence-informed adherence models to guide practice and research.…”
Section: Introductionmentioning
confidence: 99%
“…Rigorous research and in-depth review has been identified as a critical limiting factor to the development of much needed adherence-informed tools for health care professionals. 12 , 13 Relevant published literature broadly assigns methods for measuring adherence into two categories, direct and indirect, based upon mode of observation employed by each. To begin to distinguish relative value among many measures, Table 1 describes both direct and indirect measures and denotes advantages for each.…”
Section: Matching the Hammer To The Nail – Purposeful Measurementmentioning
confidence: 99%